Urgensi Penyelesaian Dugaan Kesalahan Medis Melalui Restorative Justice - Hafizah, Hildayastie; Fitriasih, Surastini (Universitas Semarang, 2022)
The purpose of this study is to examine and analyze efforts to resolve alleged medical errors through mediation as a Restorative Justice approach and developments in several developed countries such as America, Japan, and Canada as a basis for comparison. This research needs to be discussed more deeply because the dispute should be mediated through a Restorative Justice approach as a reference for legal reform in Indonesia, this approach aims to